Quantum-inspired optimization for wavelength assignment - Boev, Aleksey S.; Usmanov, Sergey R.; Semenov, Alexander M.; Ushakova, Maria M.; Salahov, Gleb V.; Mastiukova, Alena S.; Kiktenko, Evgeniy O.; Fedorov, Aleksey K. (Frontiers in Physics, 2023)
Problems related to wavelength assignment (WA) in optical communications networks involve allocating transmission wavelengths for known transmission paths between nodes that minimize a certain objective function, for example, the total number of wavelengths. Playing a central role in modern telecommunications, this problem belongs to NP-complete class for a general case, so that obtaining optimal solutions for industry relevant cases is exponentially hard. In this work, we propose and develop a quantum-inspired algorithm for solving the wavelength assignment problem. We propose an advanced embedding procedure for this problem into the quadratic unconstrained binary optimization (QUBO) form having a logarithmic improvement in the number of iterations with price-to-pay being a slight increase in the number of variables (``spins''). Then we compare a quantum-inspired technique for solving the corresponding QUBO form against classical heuristic and industrial combinatorial solvers. The obtained numerical results indicate on an advantage of the quantum-inspired approach in a substantial number of test cases against the industrial combinatorial solver that works in the standard setting. Our results pave the way to the use of quantum-inspired algorithms for practical problems in telecommunications and open a perspective for the further analysis of the employ of quantum computing devices.